EVALUASI TATAKELOLA PROGRAM STUDI PROGRAM PASCASARJANA UNIVERSITAS RIAU - Nardi "; Ernawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research is motivated by the issuance of Decree Rector No: 302 / H / 19 / AK /2009 on Management Program of Magister Studies, University of Riau, based on surveyresults that occur dualism of leadership or command in the management of the MagisterStudies Program is to courses monodisiplin responsible Director of Magister academic field,while the source of finance and personnel to the Dean of the Faculty. Meanwhile for StudiesMonodisiplin responsible academic, financial and personnel to the Director of the MagisterProgram.The object of this study is Knowing and analyzing the management Studies Programof Magister Program University of Riau by adopting the theory of William M. Dunnevaluation consisting of several indicators of effectiveness, efficiency, adequacy, equity ,responsiveness, and accuracy regarding governance made by the Director of the GraduateProgram, University of Riau.The method used in this research is descriptive qualitative method troubleshootingprocedures are examined using describing how the data obtained from observations ofliterature and field observations, then analyzed and interpreted to provide conclusions.Based on the research that there are still shortcomings and constraints inmanagement studies program of Magister Program of Riau University based on indicators ofeffectiveness, efficiency, adequacy, equity, responsiveness, and accuracy that certainly needsattention in order to improve services to students.Keywords : effectiveness, efficiency, adequacy, equity, responsiveness, accuracy